Fertilisation of agricultural soils with municipal biosolids: Glyphosate and aminomethylphosphonic acid inputs to Québec field crop soils - Charbonneau, Ariane; Lucotte, Marc; Moingt, Matthieu; Blakney, Andrew J.C.; Morvan, Simon; Bipfubusa, Marie; Pitre, Frédéric E. (The Science of the total environment, 2024)
Municipal biosolids (MBS) are suggested to be abundant, sustainable, inexpensive fertilisers, rich in phosphorus and nitrogen. However, MBS can also contain glyphosate and phosphonates that can degrade to AMPA. Glyphosate-based herbicides (GBH) are used in field crops all over the world. Most glyphosate generally degrades within a few weeks, mainly as aminomethylphosphonic acid (AMPA). AMPA is more persistent than glyphosate, and can accumulate from one crop year to the next. AMPA is phytotoxic even to glyphosate-resistant crops. The aims of this study were to assess whether MBS applications constitute: 1) an additional source of glyphosate and AMPA to agricultural soils with respect to GBH, 2) a significant source of trace metals, and 3) a partial replacement of mineral fertilisation while maintaining similar yields. To this end, four experimental agricultural sites were selected in Québec (Canada). Soil samples (0–20 cm) were collected to estimate the as yet unmeasured contribution of MBS application to glyphosate and AMPA inputs in agricultural soils. MBS applied in 2021 and 2022 had mean concentrations of 0.69 ± 0.53 μg glyphosate/dry g and 6.26 ± 1.93 μg AMPA/dry g. Despite the presence of glyphosate and AMPA in MBS, monitoring of these two compounds in corn and soybean crops over two years showed no significant difference between plots treated with and without MBS applications. For the same site, yields measured at harvest were similar between treatments. MBS application could thus represent a partial alternative to mineral fertilisers for field crops, while limiting the economic and environmental costs associated with their incineration and landfilling. It is also an economic advantage for agricultural producers given the possibility of using fewer mineral fertilisers and therefore reducing the environmental impact of their use. [Display omitted] •Municipal biosolids (MBS) offer significant potential for fertilising field crops.•MBS contain significant amounts of both glyphosate and AMPA.•Soil chemistry and crop yields were followed in MBS treated and untreated plots.•Glyphosate and AMPA contents in soil do not increase with MBS treatment.•MBS are a good substitute for mineral fertilisers leading to similarly crop yields.